Monitoring Cleaning and Disinfection in a Respiratory Syndrome Unit Amid the SARS-CoV-2 Pandemic - Rigonato, Elaine Mazuqui; Gonçalves, Viviane Perbeline; Angeloni, Natália Liberato Norberto; Maronesi, Maria Luisa Pereira; Rocha, Daniel de Macedo; Valle, Lomberto Ariel Romeu; Lima, Helder de Pádua; Santos Junior, Aires Garcia dos (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: This study aimed to monitor the cleaning and disinfection processes of surfaces in a respiratory syndrome unit. Design: A cross-sectional study conducted in a respiratory syndrome unit specialized in the treatment of COVID-19. High-touch surfaces were monitored using the following methods: Adenosine Triphosphate (ATP), Colony-Forming Units (CFU), and Visual Inspection. Monitoring lasted for 30 days, with samples collected both before and after the team performed the cleaning and disinfection procedures. Results: The results showed that most surfaces had microbial counts above 2.5 CFU/cm² both before and after cleaning, thus failing the test. Only one surface showed significant differences in relation to the adenosine triphosphate method: the patients’ chair (P=0.014). Regarding visual inspection, it was observed that defects in the structure of the monitored surfaces impacted non-compliance rates. Additionally, a lack of standardization in the use of cleaning products was noted. Implications: The study highlighted the need for improvements in the process to meet the values proposed in the literature, ensuring a safe environment in all healthcare services. It also underscored the complexity of patients with respiratory syndrome.